An FR4‐based dc to 60 GHz substrate integrated suspended line to suspended coplanar waveguide transition. Issue 2 (19th October 2021) - Wu, Xu; Ma, Kaixue; Wang, Yongqiang; Yan, Ningning; Wang, Keping
Abstract: An FR4‐based dc to 60 GHz transition from substrate integrated suspended line (SISL) to suspended coplanar waveguide (SCPW) is proposed in this letter. The design is fabricated using standard multilayer printed circuit boards (PCB) technology, and the substrates used are all low‐cost FR4. Since the whole structure is in the suspended form, the bandwidth of the transition has been expanded three times when compared with the state of art. By using SISL with double‐metal layer and patterned substrate, the loss of the transition is further reduced, and the conductor loss and dielectric loss have been individually analyzed. The results show that the proposed back‐to‐back transition has an insertion loss of less than 2.7 dB and a return loss of better than 11.4 dB from dc to 60 GHz.